Aspiration - Symphony in the Flint Hills, Inc. (Symphony in the Flint Hills, 2019)
Introduction: "In these days of great trouble and unrest, it is good to have something outside our own planet, something fine and distant and comforting for troubled minds. Let people look to the stars for comfort and find solace as others have." – Annie Jump Cannon, 1941. In the beginning there were the heavens and the earth, and those on earth looked to the heavens for meaning.